Analysis of the Phialocephala subalpina Transcriptome during Colonization of Its Host Plant Picea abies. - Vanessa Reininger; Markus Schlegel (PLoS ONE, 2016)
BACKGROUND:Phialocephala subalpina belongs to the Phialocephala fortinii s.l.-Acepphala applanata species complex (PAC) forming one of the major groups belonging to the dark septate endophytes (DSE). Depending on the strain, PAC was shown to form neutral to pathogenic associations with its host plant Picea abies. To understand PACs lifestyle we investigated the effect of presence/absence of Picea abies on the transcriptome of strain 6_70_1. MATERIALS AND METHODS:PAC strain 6_70_1 was grown in liquid Pachlewski media either induced by its host plant Picea abies or without host plant as a control. Mycelia were harvested in a time course (1, 2, 3, 4, 7, 11, 18 days) with and without induction by the host plant and the fungal transcriptome revealed by Illumina sequencing. Differential gene expression analysis over the time course comparing control and treatment at each time point using the 'edgeR glm approach' and a gene enrichment analysis using GO categories were performed. RESULTS:The three main functional groups within differentially expressed genes were 'metabolism', 'transport' and 'cell rescue, defense and virulence'. Additionally, genes especially involved in iron metabolism could be detected by gene set enrichment analysis. CONCLUSION:In conclusion, we found PAC strain 6_70_1 to be metabolically very active during colonization of its host plant Picea abies. A major shift in functional groups over the time course of this experiment could not be observed but GO categories which were found to be enriched showed different emphasis depending in the day post induction.